Genetics of dependence - Abay, Ercan; Ateş, İbrahim (Journal of Dependence, 2001)
As a result of new findings on the area of molecular genetics, there is growing interest on the genetic aspects of psychiatric disorders. Genetic aspects of dependence of alcohol, tobacco and other psychoactive substances have recently been studied and important information about the candidate genes is obtained. In this review, dopaminergic system which plays an important role on dependence behavior ; human and animal studies on the genetics of dependence and "reward deficiency syndrome" is mentioned.
Keywords: Alcohol dependence; sociodemographic variables; clinical characteristics; gender; treatment outcomes